A teoria do professor reflexivo na prática docente: estudos bibliográficos - Miranda, Viviane Regina de (2021)
This research addresses considerations about the theory of the reflective teacher in teaching practice and proposes a critical and intentional reflection arising from the teacher's practice and action within the school, when observing and reflecting to solve the problems encountered in the classroom. In order to promote contributions about the theme and the conceptions of educators about the Reflective-Teacher. Thus, we will present the contributions of theoretical contributions endorsed by Paulo Freire, Kenneth Zeichner and Donald Schön about reflective teaching practice. For that, an exploratory qualitative research was carried out on the indicated theme, using Bardin's categorical analysis. A bibliographic study was carried out in the literature in the area of reflective teacher study, articles published in journals, articles published in scientific events, as well as dissertation and theses databases in Brazil from 2010 to 2020. This research sought to indicate ways to understand teacher education reflective about the practices of the reflective teacher, identifying the difficulties and challenges that prevent the teacher from advancing in their professional practice, in order to contribute to pedagogical practice. The works analyzed show that there is a confrontation between ideas and practice, so that reflection is not an acquired habit, but built throughout the entire teaching career. The reflection of teaching practice is something complex, and the reflective teaching movement encourages reflection based on a cycle, the process of reflection, in order to expand the critical, decision-making power of teachers about their profession and the best way to exercise it. in order to promote autonomy and emancipation.